Incidence of dental barotrauma and temporomandibular joint problems of divers in Turkey - DUMLU, ASIM; ALTUN, BÜŞRA DİLARA (My University, 2023)
Introduction: In this study, we aimed to examine dental barotrauma and temporomandibular joint (TMJ) complaints in a large group of divers. Methods: This survey study included scuba divers older than 18. The questionnaire contained 25 questions about the demographic characteristics of divers, dental health behaviors, and diving-related dental, sinus and/or temporomandibular joint pain. Results: The study group consisted of 287 instructors, recreational and commercial divers (mean age 38.96 years) (79.1% males). A total of 46% of divers reported a frequency of tooth brushing less than twice a day; 28% never receive a routine dental examination; 22.6% experienced dental pain after and/or during diving, mostly in the upper posterior teeth (40%); 17% required dental treatment; 77% of these cases are restoration fracture. TMJ symptoms after diving were statistically significantly higher in women (p=0.04). Jaw and masticatory muscle pain in the morning (p≺0.001) limitation of mouth opening (p=0.04) and joint sounds in daily life (p≺0.001) were recorded as exacerbated after diving; the results were found to be statistically significant. Conclusion: In our study, the localization of barodontalgia was consistent with the distribution of caries and restored tooth areas in the literature. Dive-related TMJ pain was also more common in those with pre-dive problems such as bruxism and joint noise. Our results are important to remind us of the necessity of preventive dentistry practices and early diagnosis of problems in divers. Divers should take personal precautions, such as brushing their teeth twice a day and avoiding the need for urgent treatment. The use of a personalized mouthpiece is also recommended for divers to prevent dive-related temporomandibular joint diseases.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; SOLUNUM SİSTEMİ; FİZYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; RESPIRATORY SYSTEM; PHYSIOLOGY; Akciğer ve Solunum Tıbbı; Fizyoloji (tıbbi); Pulmonary and Respiratory Medicine; Physiology (medical); barotrauma; diving; preventive dentistry; soft- temporomandibular joint disorders; soft- women